Workplace aggression as cause and effect: Emergency nurses' experiences of working fatigued. (July 2017) - Wolf, Lisa A.; Perhats, Cydne; Delao, Altair M.; Clark, Paul R.
Highlights: Fatigue compromises nurses' personal lives and creates a toxic unit environment. Fatigue compromises safe patient care. Below-adequate staffing levels are a major source of fatigue. Lateral violence (workplace bullying) is both a cause and effect of fatigue. Abstract: Introduction: Emergency nursing requires acute attention to detail to provide safe and effective care to potentially unstable or critically ill patients; this requirement may be significantly impaired by physical and mental fatigue. There is a lack of evidence regarding the effects of fatigue caused by factors other than a sleep deficit (e.g., emotional exhaustion). Fatigue affects nurses' ability to work safely in the emergency care setting and potentially impacts their health and quality of life outside of work. Methods: This was the qualitative arm of a mixed methods study; we used a qualitative exploratory design with focus group data from a sample of 16 emergency nurses. Themes were identified using an inductive approach to content analysis. Results/discussion: The following themes were identified: "It's a weight on your back;" "Competitive nursing;" "It's never enough;" "You have to get away;" and "Engagement as a solution." Conclusions: Our participants reported high levels of fatigue, which compromised patient care, had a negative effect on their personal lives, and created a toxic unit environment. They reported lateral violence as both the cause and effect of mental and emotional fatigue, suggesting that unit culture affects nurses and the patients they care for.